THE EFFECTS OF PROFESSIONALISM, INDEPENDENCE, ORGANIZATIONAL COMMITMENT AND WORKLOAD ON AUDITOR PERFORMANCE (Empirical Study on Auditors of the Riau Provincial Inspectorate) - Irdana, Leydis Nevi; Novius, Andri (LPPM STMIK Dharmapala Riau, 2025)
This study aims to determine whether professionalism, independence, organizational commitment, and workload have an effect on Auditor Performance at the Riau Provincial Inspectorate in 2025. The population in this study were auditors working at the Riau Provincial Inspectorate. The sampling technique used saturated sampling so that the total sample was 63 auditors. Data analysis used the classical assumption test and hypothesis testing using the SPSS version 30 tool. The results of the study showed that professionalism and organizational commitment had a significant effect on auditor performance. While independence and workload did not affect auditor performance. The results of the Adjusted RSquare test show that the independent variables used in this study can explain the dependent variable by 51% while the remaining 49% is influenced by other variables not examined in this study.